2004
DOI: 10.1007/s11207-005-4981-y
|View full text |Cite
|
Sign up to set email alerts
|

Did Open Solar Magnetic Field Increase During The Last 100 Years? A Reanalysis of Geomagnetic Activity

Abstract: Abstract. Long-term geomagnetic activity presented by the aa index has been used to show that the heliospheric magnetic field has more than doubled during the last 100 years. However, serious concern has been raised on the long-term consistency of the aa index and on the centennial rise of the solar magnetic field. Here we reanalyze geomagnetic activity during the last 100 years by calculating the recently suggested IHV (Inter-Hour Variability) index as a measure of local geomagnetic activity for seven station… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 5 publications
8
64
0
Order By: Relevance
“…the same time as the larger calibration glitch in the original IDV) and so wrongly concluded that there was no change at all in solar and interplanetary magnetic fields. Using other stations, Mursula et al (2004) found that the calibration of this original version of IHV was indeed poor and so Svalgaard et al (2003) revised their estimates using more stations (lowering their estimate of the calibration error in aa to 5.2 nT and so acknowledging for the first time that at least some of the drift in aa was solar in origin). However, Mursula and Martini (2006) showed that about half of this difference was actually caused by an inhomogeneity in the IHV data series, namely that Svalgaard et al (2003) had used spot values for the early years and hourly means in later years.…”
Section: The Ihv Indexmentioning
confidence: 99%
“…the same time as the larger calibration glitch in the original IDV) and so wrongly concluded that there was no change at all in solar and interplanetary magnetic fields. Using other stations, Mursula et al (2004) found that the calibration of this original version of IHV was indeed poor and so Svalgaard et al (2003) revised their estimates using more stations (lowering their estimate of the calibration error in aa to 5.2 nT and so acknowledging for the first time that at least some of the drift in aa was solar in origin). However, Mursula and Martini (2006) showed that about half of this difference was actually caused by an inhomogeneity in the IHV data series, namely that Svalgaard et al (2003) had used spot values for the early years and hourly means in later years.…”
Section: The Ihv Indexmentioning
confidence: 99%
“…The significance of this work is that Eskdalemuir data are widely used in studies concerning long-term trends in magnetic field variability and inferred solar variability (for example Mursula et al, 2004;Svalgaard and Cliver, 2007b). For that reason inconsistencies and errors in the Eskdalemuir time series need to be identified and carefully corrected.…”
Section: Discussionmentioning
confidence: 99%
“…Lockwood et al, 1999) as it is the longest running index of magnetic activity available, dating back to 1868. However some records of observatory hourly values are also very long and this lead to the development and analyses of IHV indices for inferring long-term changes in the Sun and near-Earth space (Svalgaard et al, 2004;Mursula et al, 2004;Mursula and Martini, 2006;Svalgaard and Cliver, 2007a, b). The problem with the Eskdalemuir IHV series was known at this stage and attempts were made to correct it .…”
Section: The Discoverymentioning
confidence: 99%
“…It is empirically defined but its physical meaning is not yet clear. There is a long list of studies on long-term evolution of the geomagnetic activity and its relationship with the solar variability, such as those published by Feynman & Crooker (1978), Svalgaard (1978), Cliver et al (1996), Andreasen (1997), Cliver et al (1998), Stamper et al (1999), Lockwood et al (1999), Richardson et al (2002), Mursula et al (2001), Svalgaard et al (2003), Echer et al (2004), Svalgaard et al (2004), Mursula et al (2004), Le Mouël et al (2005, Clilverd et al (2005), Svalgaard & Cliver (2005), Svalgaard & Cliver (2007), Rouillard et al (2007), Lockwood et al (2009), Feynman & Ruzmaikin (2011), Du (2011, Richardson & Cane (2012a, 2012b.…”
Section: Long-term Evolution Of the Geomagnetic Responsementioning
confidence: 99%